Determination of the Optimal Premium for the Economically Active and Inactive Population in Health Insurance in Slovakia - Špirková, Jana; Laco, Peter; Kráľ, Pavol; Štrangfeldová, Jana (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Health insurance in the Slovak Republic is the main source of the health system funding. It consists of contributions from employees, employers, self-employed, by the voluntary insured person and the state from the state budget for economically inactive population. These contributions are set by the assessment bases and corresponding percentage rates. For employees and employers, the assessment basis corresponds to employee's gross salary, for self-employed this basis is determined by the income, for the voluntarily insured person and for state insured persons the basis of assessment is defined by the average gross salary in the national economy. Due to cumulated debt in the health system of Slovak Republic, which may continue to arise as a result of lack of financial resources and continually rising expenses, there is a need for persistent reevaluation of these resources. The increase of the health insurance payments is undesirable for economically active population. For this reason, our aim is to determine the optimal percentage rate, so the optimal state conscription from the state budget for the state insured (economically inactive) and also for economically active population
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 453-460
Keywords: hea1th care; insurance; premium rate; gross salary